1992
DOI: 10.1007/bf01203828
|View full text |Cite
|
Sign up to set email alerts
|

Effects of superoxide dismutase on mouse in vitro fertilization and embryo culture system

Abstract: These results indicate that the addition of SOD exerts a protecting effect from oxidative stress both on sperm viability and on the development of embryos fertilized in vitro as well as in vivo, while its addition showed no effect on the process of fertilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…This result is consistent with previous observations (Loutradis et al 1987;Nureddin et al 1990; Bastias et al 1993). Free oxygen radicals have been shown to be generated from xanthine oxidase and HX reactions under embryo culture conditions (Goto et al 1993;Iwata et al 1999); moreover, free oxygen radicals (high O 2 tension) negatively affect embryo development (Nonogaki et al 1992;Takahashi et al 1996). In the present study, we have observed no detrimental effect of HX when embryos are cocultured with goat OECs, especially with 1-day confluent monolayers, and HX concentrations do not differ significantly in the medium.…”
Section: Discussionsupporting
confidence: 95%
“…This result is consistent with previous observations (Loutradis et al 1987;Nureddin et al 1990; Bastias et al 1993). Free oxygen radicals have been shown to be generated from xanthine oxidase and HX reactions under embryo culture conditions (Goto et al 1993;Iwata et al 1999); moreover, free oxygen radicals (high O 2 tension) negatively affect embryo development (Nonogaki et al 1992;Takahashi et al 1996). In the present study, we have observed no detrimental effect of HX when embryos are cocultured with goat OECs, especially with 1-day confluent monolayers, and HX concentrations do not differ significantly in the medium.…”
Section: Discussionsupporting
confidence: 95%
“…It is interesting to observe that blastocyst development in vitro always lags behind blastocyst development in vivo, as there is a variation in the ability of IVF media and its components to scavenge ROS and prevent DNA damage. Addition of the enzymatic antioxidant, for example SOD, to the culture medium prevented the deleterious effects of oxidative stress on sperm viability and on the embryo development both in vivo and in vitro [85]. This effect was demonstrated by increased development of two-cell stage embryos to the expanded blastocyst stage in the SOD-supplemented medium.…”
Section: Role Of Antioxidant Supplementationmentioning
confidence: 87%
“…However, additional extracellular protection against superoxide anion toxicity seems also to be required in vivo as well as in vitro since Cu/Zn SOD has been found in oviduct and uterine secretion in the mouse (Chun et al, 1994) and rabbit . Several studies have shown that supplementation of culture media with Cu/Zn SOD had a favorable effect on embryo development in bovine (Lauria et al, 1994;Fujitani et al, 1997), mouse Nonogaki et al, 1992) and rabbit (Li et al, 1993).…”
Section: Discussionmentioning
confidence: 99%